An adaptive tuned vibration absorber based on multilayered MR elastomers. (16th March 2015) - Sun, Shuaishuai; Deng, Huaxia; Yang, Jian; Li, Weihua; Du, Haiping; Alici, Gursel; Nakano, Masami
Abstract: Adaptive tuned vibration absorbers (ATVAs) featuring magnetorheological elastomers (MREs) have attracted considerable research interests because of the advantages of fast response, controllable frequency, and broad working range. Generally, the ATVA uses single layer of MRE sheet, which has some issues such as small oscillator stroke and being effective only on high frequency. In this research, an ATVA which incorporates multilayer MRE sheets was designed and prototyped. Its performance under various scan frequencies was tested on a horizontal vibration platform. A theoretical model was proposed to predict the MRE absorber performance. For the clear demonstration of the advantages of multilayered MRE absorber, two kinds of absorbers with only one layer of MRE were prepared as comparison. The experiments compared the vertical support capability and the tuning frequency range of these two ATVAs, which have clearly highlighted the capabilities of multilayered MRE absorber with larger oscillator stroke (as large as 13.6 mm) and lower working frequencies (as low as 3.2 Hz). The vibration absorption evaluation was conducted by mounting the multilayered MRE absorber on a single-degree-of-freedom system. The results identify that the ATVA with multilayered MREs could work lower than 10 Hz, which is very difficult for the one with single layer MRE. Additionally, the performance of the passive and adaptive tuned laminated MRE absorbers on attenuating a swept frequency vibration are presented, respectively. The ATVA was more effective than the passive absorber over a wide frequency range.